A microscopy study of the structural features of post-LASIK human corneas. - Mohammad Abahussin; Sally Hayes; Henry Edelhauser; Daniel G Dawson; Keith M Meek (PLoS ONE)
Purpose To study the structural features of human post-LASIK corneas. Methods A pair of post-mortem donor corneas, from a 55-year old patient who underwent uncomplicated LASIK surgery five years previously, were bisected and fixed in 4% paraformaldehyde. The right cornea and one half of the left cornea were processed for light microscopy and scanning electron microscopy. One half of the right cornea was also examined by transmission electron microscopy. Results The flap-bed interface could be easily detected several years after LASIK and, although the flap appeared to be in close association with the stromal bed, there was a noticeable absence of reconnection between adjacent severed lamellae. Tissue gaps were evident at the flap margin, which once free of cellular components revealed the presence of a few bridging fibres. Conclusion Examination of corneas five years after LASIK revealed evidence of primitive reparative scar development at the wound interface, but no reconnection of severed collagen lamellae. Such findings may explain the occurrence of flap dislocation following trauma in some patients months or years after surgery.